A novel strategy for the management of cytomegalovirus retinitis in immunocompromised patients using new anti-cytomegalovirus drugs - Yao, Yuou; Zeng, Qiaozhu; Sun, Yaoyao; Jin, Enzhong; Tang, Jiyang; Cai, Yi; Hou, Jing; Miao, Heng (Frontiers in Medicine, 2025)
ObjectivesThis study presents four cases of cytomegalovirus retinitis (CMVR) managed using a novel antiviral strategy, aiming to preliminarily assess its efficacy and safety profile.MethodsA retrospective chart review was conducted on four patients (seven eyes) diagnosed with CMVR at Peking University People’s Hospital. All patients received oral letermovir or maribavir as the primary treatment. Weekly intravitreal injections of high-dose (6 mg) ganciclovir (IVG) were administered to those with macula involvement or aggressive lesions during the initial treatment. Data on demographics, ophthalmic examinations, laboratory results, and clinical outcomes were analyzed.ResultsAll four patients showed clinical and fundoscopic improvement, achieving complete resolution of retinitis. However, one patient developed bilateral retinal detachment requiring vitrectomy. Initial administration of high-dose IVG ensured rapid stabilization of the aggressive or macula-threatening lesions. While subsequent oral antiviral maintenance significantly reduced the need for repeated IVG injections. Both letermovir and maribavir demonstrated excellent tolerability with no adverse events observed.ConclusionThis novel therapeutic strategy provides safe and effective treatment option for CMVR, particularly promising for patients with complex systemic comorbidities.